Optimizing CO2 Storage Strategies for Enhanced MineralTrapping and Plume Containment in The Aquifer Zoneof an Indonesian Gas Reservoir - Iskandar, Utomo Pratama; Arik; Panuju; Grandis, Garindia; Ilham, Nanda (Scientific Contributions Oil and Gas, 2026)
This study evaluates optimized CO₂ storage strategies in the aquifer zone of the SK gas field in Indonesia to improve plume containment and explore the potential for enhanced mineral trapping. A coupled compositional-flow and reactive-transport simulation workflow was applied using an upscaled reservoir model under a common safe operating pressure envelope and a containment constraint requiring the plume to remain within the aquifer zone over a 120-year simulation period. Three groups of scenarios were examined: well-placement sensitivity (A1–A3), production-assisted injection (B1–B3), and completion-design sensitivity (C1–C3). Among the baseline cases, A3 provided the best plume containment, with the most compact lateral footprint and smallest vertical plume spread, while A1 gave the highest total stored CO₂. Among the production-assisted cases, B2 was the most effective pressure-management option, producing the largest pressure reduction and a modest increase in total stored CO₂. Completion redesign generated the largest storage gains, increasing total stored CO₂ by about 28–33.3% relative to the corresponding baseline cases. Most scenarios maintained the plume confinement within the aquifer zone, although C1 showed localized upward CO₂ occurrence near the free-water level. Overall, the tested strategies improved storage performance, with A3 providing the best plume containment among the baseline cases, B2 delivering the strongest pressure-management benefit and increasing total stored CO₂ by approximately 3.93% relative to A2, and completion redesign producing the largest storage gains, increasing total stored CO₂ by about 28–33.3% relative to the corresponding baseline cases. Mineral trapping increased slightly in the completion-design cases, although it remained a minor component of total storage within the 120-year simulation period.